Natural radionuclide and toxic metal contents of rock salts from mines in Central Anatolia of Turkey - Hançerlioğullari, A.; Eyüboğlu, K. (Informa UK Limited, 2020)
In this study, the natural radionuclide andpotentially toxic heavy metal contents of rock salt samples collected from three different salt mines located in Cankiri city in the Central Anatolia of T...